O currículo projetado e o currículo vivido no curso de graduação em Administração da Pontifícia Universidade Católica de São Paulo: o projeto pedagógico e o ensino e aprendizagem da pesquisa sob a ótica dos professores - Tudda, Luciane (2011)
The central theme of this work is the inclusion of research activities in the undergraduate Administration Curriculum of the Pontifical Catholic University of São Paulo (PUC-SP). The object is to show the curriculum in action as seen by the faculty; and to support the building of a continuous evaluation process of both the teaching and the learning of research, so as to sustain and consolidate the programme's activities, and to contribute to its improvement. The main sources are Andrade, Amboni, Covre, Demo, Imbernón, Martins, Pimenta, Anastasiou, Sacristán, Severino, Sguissardi, Szymanski, Almeida, Prandini, Tardif e Lessard. The writer has opted for a qualitative approach, incorporating subsidies from quantitative research; as well as from bibliographic, documental and field research. As a strategy for the collection of data, reflexive semi-structured interviews were conducted, in order to generate understanding of how these activities were proposed in the programme's Educational Project, how they were implanted, and how they are experienced by the docents. Bibliographic and documental analysis of the data obtained has made it possible to display the results of field research. The insertion of research activities into the programme is understood by the majority of the programme's managers and faculty members as an advance in terms of the students' education; and as a means of presenting the challenges encountered in the day-to-day, as well as alternative paths proposed for the enhancement and consolidation of research within the undergraduate Administration programme of PUC-SP